The afterlife imagery in Luke's story of the rich man and Lazarus - Lehtipuu, Outi. (Supplements to Novum Testamentum,, 2007)
Despite the keen scholarly interest in the Gospel parables, the afterlife scenery in the story of the rich man and Lazarus has often been overlooked. Using insights from the orality studies and intertextuality, the author places the Lukan description of the fate of the dead into the larger Hellenistic matrix, provided by a large number of Greco-Roman and Jewish sources, both literary and epigraphic. Moreover, she challenges several conventional stances in Lukan studies, such as tracing the original of the story to Egypt, or maintaining that eschatology is a key for understanding Luke's work and the purpose for writing it, or harmonizing Luke's eschatological thinking by positing an intermediate state between death and general resurrection. Thus, the book offers fresh insights both to the way the fate of the dead was understood in the ancient world and to the concept of Lukan eschatology.